Folic acid-modified celastrol nanoparticles: synthesis, characterization, anticancer activity in 2D and 3D breast cancer models - Siukan Law; Albert Wingnang Leung; Chuanshan Xu (Artificial Cells, Nanomedicine, and Biotechnology)
Celastrol is used in traditional Chinese medicine for treating cancers. However, its low water solubility and poor tumour selection represent major pitfalls for clinical application. In the present study, gold nanoparticle (AuNP) firstly was conjugated with PVP-co-2-dimethylaminoethyl methacrylate (Polymer) and celastrol then modified by folic acid. The as-prepared folate receptor-targeted celastrol AuNP (FCA) was characterized using attenuated total reflection Fourier transform infrared spectroscopy, UV-Vis spectrometry, transmission electron microscope, and inductively coupled plasma mass spectrometry. The physical properties of FCA were also determined in solubility, drug encapsulation and in vitro drug release. Its anticancer activities were assessed in the 2D and 3D breast cancer models. The results showed that FCA was synthesized successfully with good solubility, high encapsulation efficiency and loading content. FCA showed the optimal cumulative release at pH 5.0 and high cellular uptake and exhibited significant inhibition on breast cancer cells. FCA also induced more significant apoptosis either in 2D and 3D breast cancer model than the celastrol AuNP and celastrol alone. These findings demonstrate that FCA improves water solubility of celastrol and enhances its anticancer activities against breast cancer. FCA might be a potential candidate of anticancer drug for breast cancer in the future if further development.